Muḥammad : Hindu kitābon̲ men̲ - Ibn-i Akbarulʻaẓamī. (Lāhaur : Intik̲h̲āb-i Jadīd Pres, 1998)
On the life of Prophet Muhammad, d. 632 as interpreted in Hindu and other non-Muslim books.
In Urdu; some in Hindi.
P. 151-152 blank.
committed to retain
Keywords: Muḥammad, -- Prophet, -- -632.; Islam -- Relations -- Hinduism; Hinduism -- Relations -- Islam; Muḥammad, -- Prophet, -- -632.; Hinduism; Interfaith relations; Islam